Edukasi Anak Terkait Protokol Kesehatan Dalam Pencegahan COVID-19 di SDN 003 Sanga-Sanga - Lubis, Bachtiar Safrudin; Oktaviani, Anisa (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2023)
The increasing number of Covid-19 cases in Indonesia has a significant health impact on the community. The growth of the Covid-19 virus sticks to the hands every day through physical contact with the environment, and some of them can cause or cause various diseases. These microorganisms need to be destroyed or prevented from spreading, one of the easiest and most appropriate ways is with the 3 M, namely increasing knowledge related to Covid-19, and processes through washing hands, wearing masks and removing masks. This service activity aims to provide knowledge about how to prevent Covid-19. The participants of the activity were students of grades 4,5 and 6 at SDN 003 Sanga-sanga. The method used in this activity is in the form of lectures, discussions, practice and demonstrations. The results of the activities achieved through this activity are increasing knowledge about how to prevent Covid-19 so as to increase student awareness to work together in an effort to break the Covid-19 chain in school settings. This health education activity is expected to help health workers in Indonesia in preventing Covid-19 in schools.